Fishes of the Western North Atlantic. order Isospondyli (part), suborder Argentinoidea, suborder Stomiatoidea, suborder Esocoidea, suborder Bathylaconoidea, order Giganturoidei - Bigelow, Henry Bryant, 1879-1967; Cohen, Daniel M.; Dick, Myvanwy M.; Gibbs, Robert H., Jr; Grey, Marion; Morrow, James E. (James Edwin), 1918-2002; Schultz, Leonard P. (Leonard Peter), 1901-1986; Walters, Vladimir, 1927- (Memoir (Sears Foundation for Marine Research), 1964)
"Specialist authorships of its sections include detailed species descriptions with keys, life history and general habits, abundance, range, and relation to human activity, such as economic and sporting importance. The text is written for an audience of amateur and professional ichthyologists, sportsmen, and fishermen, based on new revisions, original research, and critical reviews of existing information. Species are illustrated by exceptional black and white line drawings, accompanied by distribution maps and tables of meristic data."--